TI_GERICHTE 14.2005.69 vom 22. August 2005 , appello contro decreto di fallimento. Solvibilità. Rappresentanza. Indennità - TI Tribunale d'appello (2005)
appello contro decreto di fallimento. Solvibilità. Rappresentanza. Indennità